2013
DOI: 10.5665/sleep.2816
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep Restriction Reduces Insulin Sensitivity in Adolescent Boys

Abstract: Klingenberg L; Chaput JP; Holmbäck U; Visby T; Jennum P; Nikolic M; Astrup A; Sjödin A. Acute Sleep Restriction Reduces Insulin Sensitivity in Adolescent Boys. 2013;36(7):1085-1090.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 27 publications
3
85
0
2
Order By: Relevance
“…Several potential biologic mechanisms may contribute to the relation of short sleep duration and diabetes. First, laboratory studies have corroborated and extended the decreases in glucose tolerance and insulin sensitivity after sleep restriction, as shown by increased hepatic glucose production and reduced peripheral glucose disposal (33)(34)(35)(36)(37). A recent research indicated that slow wave sleep suppression but not rapid eye movement sleep disturbance during nocturnal sleep plays a key role in the regulation of glucose (38).…”
Section: Results In Relation To Other Studiesmentioning
confidence: 88%
“…Several potential biologic mechanisms may contribute to the relation of short sleep duration and diabetes. First, laboratory studies have corroborated and extended the decreases in glucose tolerance and insulin sensitivity after sleep restriction, as shown by increased hepatic glucose production and reduced peripheral glucose disposal (33)(34)(35)(36)(37). A recent research indicated that slow wave sleep suppression but not rapid eye movement sleep disturbance during nocturnal sleep plays a key role in the regulation of glucose (38).…”
Section: Results In Relation To Other Studiesmentioning
confidence: 88%
“…The first study to examine the effect of experimental sleep manipulation upon insulin resistance in lean adolescents was conducted by Klingenberg and colleagues [45]. This randomized crossover study assessed 21 healthy males (mean age 16.…”
Section: Sleepmentioning
confidence: 99%
“…In healthy adolescents, two studies found that insulin sensitivity was negatively correlated to stage 1 non-rapid eye movement (non-REM) sleep, and positively to SWS duration [8,9]. Furthermore, in another population of healthy adolescents, partial sleep deprivation, with preserved SWS and a reduced amount of REM sleep, was followed by an increase in insulin resistance [10]. A correlation between short sleep duration and insulin resistance has also been found with actigraphic studies both in adolescents [11,12] and in younger children [13].…”
Section: @Erspublicationsmentioning
confidence: 99%